Effect of electron irradiation on crystallinity of polytetrafluoroethelene - Kupchishin, A.I.; Pivovarov, S.P.; Tlebaev, K.B.; Aryutkin, K.N. (Ye.A.Buketov Karaganda State University Publishing house, 2010)
Dose dependences of thermal conductivity and density of polytetrafluoroethelene (PTFE) were studied. It is found that irradiation of PTFE up to 1 MGy comes to increasing of crystallinity degree and at higher doses comes to decreasing.
Keywords: thermal conductivity; density; crystallinity; effect of irradiation; heat transition